Factors influencing distribution and habitat associations in an endemic group of temperate Western Australian reef fishes over a latitudinal gradient - Saunders, Ben; Harvey, Euan; Kendrick, G. (Inter-Research, 2014)
Similarities and differences in the density, distribution and habitat associations of 3 species from the pomacentrid genus Parma (Parma mccullochi, P. occidentalis, P. victoriae) were identified across 2000 km of temperate coastline in Western Australia. For P. mccullochi, fine-scale habitat associations were also assessed using the position of individual fish as observation points. A fourth species, the endemic P. bicolor, was rarely encountered. Satellite-derived sea-surface temperature was a good predictor of the distribution of the 3 commonly encountered species over the survey area. P. occidentalis were northerly distributed in warmer waters, P. victoriae were southerly distributed in cooler waters, while P. mccullochi were cosmopolitan over the survey area, with the highest densities recorded towards the centre of the study area. These findings suggest that eco-physiological theory may be applicable to describing the distribution of these, and similar, species. Similar habitat associations were observed for the 3 commonly encountered species and, in the case of P. mccullochi, at a range of spatial scales. All species were associated with vertical or overhanging rock walls and avoided areas of continuous algal canopy. P. occidentalis and P. mccullochi were associated with turfing and understorey algal forms. As the species use similar habitats, we suggest that where their distributions overlap they will experience niche overlap and resource competition. While each species may occupy different fundamental niches defined by different sea-surface temperature requirements, further study may reveal that competition for resources between these species leads to competitive displacement on both local and geographical scales.